Numerical assessment of the interaction between shear and moment actions in LVL bolted connections. (1st September 2022) - Masaeli, Mahyar; Karampour, Hassan; Gilbert, Benoit P.; Talebian, Nima; Behnia, Arash
Abstract: Mass timber buildings are becoming the new sustainable choice in construction due to their reduced carbon footprint and benefits of prefabrication. As the height of timber buildings increases and floors with longer spans are employed, the role of connections in the structural integrity becomes more noticeable. There is limited knowledge available on structural performance and ductility of bolted LVL timber connectors in combined shear and bending actions. The current study uses a series of physical tests to interpret the interaction between bolts and timber in different loading scenarios and bolt arrangements. Finite element analyses (FEA) are conducted to interpret the experimental test results and to predict the interaction behaviour of a bolted beam-to-column connection and the same connection retrofitted with self-tapping screws. Structural responses and failure modes under combined loading of each connection are discussed, and interaction curves and expressions are developed. Highlights: Failure modes of LVL double-beam to column connectors with different bolt arrangements are studied. The adopted FEA can accurately predict the response and failure modes of the connections in shear and bending. Interaction curves are proposed that cover a wide range of shear-to-bending combined actions.